Structured Clinical Documentation to Improve Quality and Support Practice‐Based Research in Headache. Issue 8 (1st August 2018) - Meyers, Steven; Claire Simon, Kelly; Bergman‐Bock, Stuart; Campanella, Franco; Marcus, Revital; Mark, Angela; Freedom, Thomas; Rubin, Susan; Semenov, Irene; Lai, Rebekah; Hillman, Laura; Tideman, Samuel; et al.
Abstract : Objective: To use the electronic medical record (EMR) to optimize patient care, facilitate documentation, and support quality improvement and practice‐based research, in a headache specialty clinic. Background: Many physicians enter data into the EMR as unstructured free text and not as discrete data. This makes it challenging to use data for quality improvement or research initiatives. Methods: We describe the process of building a customized structured clinical documentation support toolkit, specific for patients seen in a headache specialty clinic. The content was developed through frequent physician meetings to reach consensus on elements that define clinical Best Practices. Tasks were assigned to the care team and data mapped to the progress note. Results: The toolkit collects hundreds of fields of discrete, standardized data. Auto scored and interpreted score tests include the Generalized Anxiety Disorder 7‐item, Center for Epidemiology Studies Depression Scale, Migraine Disability Assessment questionnaire, Insomnia Sleep Index, and Migraine‐Specific Quality of Life. We have developed Best Practice Advisories (BPA) and other clinical documentation support tools that alert physicians, when appropriate. As of April 1, 2018, we have used the toolkits at 4346 initial patient visits. We provide screenshots of our toolkits, details of data fields collected, and diagnoses of patients at the initial visit. Conclusions: The EMR can be used to effectively structure and standardize headache clinic visits for quality improvement and practice‐based research. We are sharing our proprietary toolkit with other clinics as part of the Neurology Practice‐Based Research Network. These tools are also facilitating clinical research enrollment and a pragmatic trial of comparative effectiveness at the point‐of‐care among migraine patients.